HUBUNGAN NILAI MINI NUTRITIONAL ASSESSMENT (MNA) DENGAN LAMA RAWAT INAP - Siti Hafizhah Fatimah; Wiwit Agung Sri Nur Cahyawati; Roselina Panghiyangani (Homeostasis, 2022)
Mini Nutritional Assessment (MNA) is an instrument for assessing and screening specific nutritional in the elderly. Elderly are vulnerable to malnutrition because of physiological and functional changes that contribute to increase length of stay. The purpose of this study was to determine the correlation between Mini Nutritional Assessment value with length of stay of elderly patients at RSUD Ulin Banjarmasin. This research is analytic observational with cross-sectional method. A sample of 32 elderly patients was analysis used Spearman correlation test. The  median MNA value was 20.00 points and the median length of stay was 8.00 days. The results of the correlation test showed that the value of p = 0.002 and value of r = -0.532 which means there is a significant correlation and a strong correlation with a negative direction. It can be concluded that there is a correlation between the Mini Nutritional Assessment (MNA) value with length of stay of elderly patients in internal medicine ward at RSUD Ulin Banjarmasin.